Высокопатогенный птичий грипп и его эпизоотия среди больших бакланов в Украине в весенний период 2006 года - Чирний, В.И.; Ильичев, Ю.А.; Хайтович, А.Б. (Інститут зоології ім. І.І. Шмальгаузена НАН України, 2008)
Epizootic of highly pathogenic bird influenza, caused by circulation of a virus of influenza A subtype H5N1 among fowl and wild bids had struck 60 countries within three continents of the eastern hemisphere in 2005-2006. It appeared in the Ukraine not only amidst fowl in the Crimea AR at the end of 2005, but also among wild birds - the Cormorants (Phalacrocorax carbo) during spring period of 2006 on one of the islands in the Sivash Bay. Strains of a virus of influenza A subtype H5N1, isolated from the internal organs of these birds were highly pathogenic for Gallinaceae birds and mammalia, but had not mutations to receptors typical for man as well as mutations that cause a steadiness of virus to the main anti- influenza medicaments.